2015
DOI: 10.1177/1941738115621011
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Performance After Jones Fracture in National Basketball Association Athletes

Abstract: Background:Basketball players are at risk for foot injuries, including Jones fractures. It is unknown how this injury affects the future play and performance of athletes.Hypothesis:National Basketball Association (NBA) players who sustain Jones fractures of the base of the fifth metatarsal have high rates of return to play and do not experience a decrease in performance on return to competition when compared with preinjury and with control-matched peers.Study Design:Retrospective cohort study.Level of Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 22 publications
4
46
0
Order By: Relevance
“…Fifth metatarsal fractures, which have been previously reported in NBA 2 and NFL 5 , 14 athletes, were the most common injury requiring operative fixation in this study, followed by navicular fractures. Compared with athletes who sustained fifth metatarsal fractures, those with navicular fractures were older and had a greater number of years of professional experience ( P < 0.04).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Fifth metatarsal fractures, which have been previously reported in NBA 2 and NFL 5 , 14 athletes, were the most common injury requiring operative fixation in this study, followed by navicular fractures. Compared with athletes who sustained fifth metatarsal fractures, those with navicular fractures were older and had a greater number of years of professional experience ( P < 0.04).…”
Section: Discussionsupporting
confidence: 64%
“…While some clinical studies have reported return-to-play rates after operative treatment of Jones fractures in professional athletes, 2 , 5 , 14 performance-based outcomes in this population are generally unknown. Furthermore, less is known about the fate of other foot fractures, such as the navicular fracture, despite their high incidence.…”
mentioning
confidence: 99%
“…We obtained injury data for NBA players from Pro Sports Transactions (http://www. prosportstransactions.com), which has been used in prior research to identify player injuries in the NBA (Begly, Guss, Ramme, Karia, & Meislin, 2016;Guss et al, 2016;Leeds, Leeds, & Motomura, 2015). The data are comprehensive in listing the date a player was injured but less comprehensive in listing the date a player recovered from injury.…”
Section: Sample and Datamentioning
confidence: 99%
“…In a recent retrospective study of professional athletes, 85% of basketball players were able to return to preinjury level of function. In this study, 92% of the patients were treated operatively, 12% required reoperation, and 19% had a recurrent injury [31]. National Football League (NFL) players are also at risk for sustaining a Jones fracture due to the repetitive strain placed on the fifth metatarsal.…”
Section: Discussionmentioning
confidence: 87%